Cement Stabilized Soil Blocks Admixed with Sugarcane Bagasse Ash - Jijo James; P. Kasinatha Pandian; K. Deepika; J. Manikanda Venkatesh; V. Manikandan; P. Manikumaran (Journal of Engineering)
The study involved investigating the performance of ordinary Portland cement (OPC) stabilized soil blocks amended with sugarcane bagasse ash (SBA). Locally available soil was tested for its properties and characterized as clay of medium plasticity. This soil was stabilized using 4% and 10% OPC for manufacture of blocks of size 19 cm × 9 cm × 9 cm. The blocks were admixed with 4%, 6%, and 8% SBA by weight of dry soil during casting, with plain OPC stabilized blocks acting as control. All blocks were cast to one target density and water content followed by moist curing for a period of 28 days. They were then subjected to compressive strength, water absorption, and efflorescence tests in accordance with Bureau of Indian standards (BIS) specifications. The results of the tests indicated that OPC stabilization resulted in blocks that met the specifications of BIS. Addition of SBA increased the compressive strength of the blocks and slightly increased the water absorption but still met the standard requirement of BIS code. It is concluded that addition of SBA to OPC in stabilized block manufacture was capable of producing stabilized blocks at reduced OPC content that met the minimum required standards.